A digital method of measuring the gonial angle on radiographs for forensic age estimation. (December 2017) - Acharya, Ashith B.
Abstract: Objective: Age estimation has important legal ramifications and assessing it, particularly in living adults, can prove challenging on occasion. This paper explores the use of gonial angle in age estimation, applying a new digital method which may be suitable in elderly subjects when many/all teeth are missing. Materials and methods: A commercially available and ubiquitous software was used to measure the gonial angle on digital orthopantomographs from 100 subjects (48 males and 52 females; age range 18–89 years) which was subjected to linear regression analysis. Results: The correlation coefficient for the gonial angle on the right side ( r = 0.25) was greater than that for the left side ( r = 0.23). Both correlations were statistically significant ( p < 0.05). The regression equations derived were tested on a holdout sample ( n = 17; age range 21–71 years) and revealed a mean absolute difference of approximately ± 14 years for the two regression equations. Conclusion: Although the gonial angle may not consistently change with an increase in chronologic age, the digital method proposed here may be one of few options available for use in the elderly with minimal or no teeth seeking retirement benefits, and may be applied as a method of last resort in geriatric age prediction. Highlights: The paper proposes a new digital method of age estimation by measuring gonial angle. Statistically significant ( p < 0.05) albeit low correlation ( r = 0.25) was obtained. Error of ± 14 years in age estimation was produced for gonial angle. The suggested digital method may be applied when no other alternatives are available. The method has application in elderly living subjects but should be used guardedly.